Self-learning skills included at family education for intermediate school - Al-Otaibi, Amal Asir Ayed; Al-Sumairi, Latifa Salih (Journal of Curriculum and Teaching Methodology, 2023)
This research aimed to reveal self-learning skills included in family education books in intermediate stage. The researcher used the descriptive analytical method using content analysis approach. The researcher made a card containing self-learning skills which are used in the research: giving opinion, willingness to learn, using local resources, and self-evaluation skills. Validity and reliability of the tool were established. Content analysis was carried out according to the skills adopted in the research. Frequencies and percentages of the self-learning skills in the analysis card and standard deviations of the major skills were measured. The results showed that the arithmetic mean of the total frequencies of the self-learning skills in the family education books at the intermediate school was (21.4), and this number showed that the inclusion of self-learning skills in the books was of a moderate. The willingness to learn skills achieved (26.9) mean, the highest among the self-learning skills, with high inclusion level. While the using of local resources achieved came second with (22.7) arithmetic mean with and moderate inclusion level. And the giving opinions skills came third with (20.2) arithmetic mean and moderate level of inclusion. Finally self-evaluation skills came last with (18.1) arithmetic mean and low inclusion level. Based on the obtained results, the researcher made some recommendations and suggestions, the most important of which are: self-learning skills in family education books in intermediate stage should be revisedin order to develop them, objectives of units should support self-learning methods and skills, family education books in intermediate stage should be enhanced in order to guide students in using modern technology means, in addition electronic information resources should be mentioned in books preface or units. The researcher suggests conducting a similar study on the level of the inclusion of self-learning skills in family education books in other stages. Also, conducting studies to evaluate family education books according to self-learning skills from the teachers’ and supervisors’ point of view.